Microbial Flora Associated with the Halophyte–Salsola imbricate and Its Biotechnical Potential - Bibi, Fehmida; Strobel, Gary A.; Naseer, Muhammad I.; Yasir, Muhammad; Khalaf Al-Ghamdi, Ahmed A.; Azhar, Esam I. (Frontiers in Microbiology, 2018)
Halophytes are associated with the intertidal forest ecosystem of Saudi Arabia and seemingly have an immense potential for yielding useful and important natural products. In this study we have aimed to isolate and characterize the endophytic and rhizospheric bacterial communities from the halophyte, Salsola imbricata, In addition these bacterial strains were identified and selected strains were further studied for bioactive secondary metabolites. At least 168 rhizspheric and endophytic bacteria were isolated and of these 22 were active antagonists against the oomycetous fungal plant pathogens, Phytophthora capsici and Pythium ultimum. Active cultures were mainly identified with molecular techniques (16S r DNA) and this revealed 95.7–100% sequence similarities with relevant type strains. These microorgansims were grouped into four major classes: Actinobacteria, Firmicutes, β-Proteobacteria, and γ-Proteobacteria. Production of fungal cell wall lytic enzymes was detected mostly in members of Actinobacteria and Firmicutes. PCR screening for type I polyketide synthases (PKS-I), type II polyketide synthases (PKS-II) and nonribosomal peptide synthetases (NRPS) revealed 13 of the 22 strains (59%) were positive for at least one of these important biosynthetic genes that are known to be involved in the synthesis of important antibiotics. Four bacterial strains of Actinobacteria with potential antagonistic activity including two rhizobacteria, EA52 (Nocardiopsis sp.), EA58 (Pseudonocardia sp.) and two endophytic bacteria Streptomyces sp. (EA65) and Streptomyces sp. (EA67) were selected for secondary metabolite analyses using LC-MS. As a result, the presence of different bioactive compounds in the culture extracts was detected some of which are already reported for their diverse biological activities including antibiotics such as Sulfamethoxypyridazine, Sulfamerazine, and Dimetridazole. In conclusion, this study provides an insight into antagonistic bacterial population especially the Actinobacteria from S. imbricata, producing antifungal metabolites of medical significance and characterized taxonomically in future.